The Impact of Bank Liquidity on the Profitability of Commercial Banks: An Applied Study on Jordanian Commercial Banks for the Period (2013/2017) - Alali, Shireen Mahmoud (International Journal of Economics and Financial Issues, 2019)
The study aims at showing the effect of banking liquidity on the profitability of commercial banks in Jordan for the period 2013-2017. The liquidity was measured by the variables of (liquidity, legal liquidity, employment ratio) as well as the profitability of commercial banks as a return on equity and assets (Liquidity ratio, legal liquidity ratio, employment ratios) on the return on assets of Jordanian commercial banks. In addition, it was found that there is an effect of bank liquidity (liquidity ratio, legal liquidity ratio) On the return on equity of the Jordanian commercial banks for the period 2013-2017. It also found that the impact of bank liquidity (liquidity ratio, legal liquidity ratio, employment ratios) on the profitability of commercial banks for the period 2013-2017 is attributable to the size of the bank. The study recommends that commercial banks should consider banking liquidity because it is of great importance in two ways. First, in the face of withdrawals from deposits, in order to avoid destabilizing the trust between the two parties, the bank and the depositors, thus leading to harm the shareholders. The second aspect is satisfying the needs of individuals with credit facilities. Therefore, commercial banks are required to measure bank liquidity and satisfy their needs because they have a negative impact on the size of bank liquidity, if it is large and with low profits, and on the other hand, the size may be low leading to bankruptcy of the bank. Keywords: bank liquidity, return on assets, return on equity, size of the bank. JEL Classifications: G2, G21 DOI: https://doi.org/10.32479/ijefi.8304